2002 Physics Education Research Conference Proceedings 2002
DOI: 10.1119/perc.2002.pr.006
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Students' Models of Sound Propagation

Abstract: We investigated students' mental models of sound propagation in introductory physics classes. In addition to the scientifically accepted wave model, students used the "entity" model. In this model sound is a self-standing entity, different from the medium, and propagating through it. All other observed alternative models are composed of entity and wave ingredients, but at the same time they are distinct from each of the constituent models. We called these models "hybrid" models. We will discuss how students us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
42
0
35

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(83 citation statements)
references
References 8 publications
6
42
0
35
Order By: Relevance
“…Just as stated in previous studies (Bao and Redish 2006, Hrepic 2002,2004, Hrepic et al 2010, Wittmann et al 2003, this study also indicated that students' mental models are context dependent. In other words, a student can use different models for the same phenomenon in different contexts.…”
Section: Model States: Context Dependency Of Mental Modelssupporting
confidence: 67%
See 2 more Smart Citations
“…Just as stated in previous studies (Bao and Redish 2006, Hrepic 2002,2004, Hrepic et al 2010, Wittmann et al 2003, this study also indicated that students' mental models are context dependent. In other words, a student can use different models for the same phenomenon in different contexts.…”
Section: Model States: Context Dependency Of Mental Modelssupporting
confidence: 67%
“…In other words, a student may use different models for the same phenomenon in different contexts. In this study, we called such usage 'mixed state' as also used in the literature (Hrepic 2002, 2004, Hrepic et al 2010. If a student uses the same model across contexts, it is called a 'pure state' (Bao and Redish 2006, Hrepic 2002, Hrepic et al 2010.…”
Section: Model States: Context Dependency Of Mental Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…blended [3,4]. Fauconnier and Turner [5] call the later process cognitive blending and they laid theoretical foundations for its understanding and further refinement [6].…”
Section: Introductionmentioning
confidence: 99%
“…In conceptual blending, two or more mental input spaces (small conceptual packets) combine to produce a blend space [5]. The need for the notion of "hybrid knowledge" [7], "hybrid" mental models [3], "synthetic" models [8], and "blended" mental models [4,9] -has emerged organically in physics education research over the past two decades in association with a wide range of physics topics (see [10] and references therein). A mental model is an internal representation that serves as a structural analogue for explaining situations and physical processes.…”
Section: Introductionmentioning
confidence: 99%